We changed the world : African Americans, 1945-1970 - Harding, Vincent; Kelley, Robin D. G.; Lewis, Earl (New York : Oxford University Press, 1997)
Examines African-American life at the close of World War II, describes the struggle for freedom and justice during the 1940s and 1950s, and discusses the explosive years of the 1960s.
American Window
Includes bibliographical references (p. 186-188) and index.
Keywords: African Americans -- Civil rights -- Juvenile literature; African Americans -- History -- 1877-1964 -- Juvenile literature; African Americans -- History -- 1964- -- Juvenile literature; African Americans -- Civil rights; African Americans -- History -- 1877-1964.; African Americans -- History -- 1964-